Securing Programmable Analog ICs Against Piracy - Elshamy, Mohamed; Sayed, Alhassan; Louerat, Marie-Minerve; Rhouni, Amine; Aboushady, Hassan; Stratigopoulos, Haralampos-G. (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2020)
In this paper, we demonstrate a security approach for the class of highly-programmable analog Integrated Circuits (ICs) that can be used as a countermeasure for unauthorized chip use and piracy. The approach relies on functionality locking, i.e. a lock mechanism is introduced into the design such that unless the correct key is provided the functionality breaks. We show that for highly-programmable analog ICs the programmable fabric can naturally be used as the lock mechanism. We demonstrate the approach on a multi-standard RF receiver with configuration settings of 64-bit words.